(3ebOeI aj GbJUGO GdJfejI (B:s (3fXQjGJ GdJfejI hfeh GSJQGJjLjGJ GdJfejI (B/s - (3TYHGfj, GSeGYjds ((3GdLRGFQ(B: s (3OGQ gheI ddfTQ hGdJhRjY(B, s, 2004)
(3fXQjGJ GdJNda(B- (3fXQjGJ GdJfejI hGdfeh(B- (3GdJfejI GdbOjeI(B- (3fXQjGJ GdJfejI hGdfeh GdMOjKI(B- (3GSJQGJjLjGJ GdJfejI aj HYV GdOhd MOjKI GdJUfjYs
Keywords: (3GdJfejI GdEbJUGOjI(B- (3fXQjGJs